Peran Public Relations dalam Komunikasi Organisasi - Aswad Ishak (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2012)
Organization is currently experiencing growth and remarkable development. An increasingly diverse public characters, both interal and external, require special handling in communicating to them. Communication activities of the organization is a strategic communications activities that need to be run by the organization. This communication activities involving management as important decision makers in the organization. Through public relations activities of the organization’s strategic communication can run well. Public relations must have the full support of management to be able to carry out the task.